COMPARATIVE STUDY ON EFFECT OF NATURAL AND SYNTHETIC SUPERDISINTEGRANTS IN THE FORMULATION OF RIZATRIPTAN BENZOATE ORAL DISPERSIBLE TABLETS - F. R., SHEEBA; CHAUDHARY, KUNDAN (International Journal of Current Pharmaceutical Research, 2020)
Objective: In the present study, the effects of a natural superdisintegrant gellan gum, karya synthetic gum superdisintegrants like sodium starch glycolate, crospovidone and combination of natural and synthetic superdisintegrant were compared in the formulations of rizatriptan benzoate oral dispersible tablets. Methods: This oral dispersible tablets were prepared by direct compression method and evaluated for weight variation, hardness, disintegration time, drug content, friability and dissolution. Drug compatibility with excipients was checked by FTIR studies. Stability study of the prepared tablets was done at 40±2°/75%±5% RH for a period of 1 mo. Results: FTIR studies showed that no any chemical interaction between drugs and excipients. The in vitro drug release study revealed that formulation F9 combination of both crospovidone and karya gum was the most successful formulation and disintegrate time within 13 seconds and drug release within 10 min. The drug release from the best formulations followed first-order kinetics, which is concentration-dependent. Short terms stability studies of the tablet for three months showed non-significant drug loss. Conclusion: The formulation containing a combination of natural and synthetic superdisintegrant was found to be the best results. Apart from fulfilling all official and other specifications, the tablets exhibited a higher rate of drug release.